PENGARUH GOOD CORPORATE GOVERNANCE, LIKUIDITAS DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR TEKNOLOGI TAHUN 2019-2023 - Rizky Rahmatullah; Rusmanto Rusmianto; Destia Pentiana (Jurnal Riset Akuntansi Soedirman, 2025)
This study aims to analyze the factors that influence financial performance. These factors include Good Corporate Governance (GCG), Liquidity, and Leverage. In this study, GCG is measured using (Independent Board of Commissioners, Audit Committee, Managerial Ownership), Liquidity is measured using the Current Ratio, and Leverage is measured using the Debt to Equity Ratio. The population used in this study were technology sector companies listed on the Indonesia Stock Exchange in 2019-2023, resulting in a population of 18 companies. Meanwhile, the sampling technique in this study used a purposive sampling method, namely using predetermined criteria, so that the data used as a sample of 11 companies. This research is a quantitative study using multiple linear regression analysis methods. The data used in this study are secondary data. The findings in this study indicate that an independent board of commissioners, audit committee, managerial ownership, and liquidity have no effect on financial performance. Meanwhile, leverage has a negative effect on financial performance.